ANALISIS PENERAPAN MODEL PEMBELAJARAN AKTIF TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PGSD SMESTER VIB UNIVERSITAS DHARMAS INDONESIA - Hader, Antik Estika (RC-INSTITUT, 2018)
One of the obstacles experienced by PGSD students who carry out field practice in school in teaching mathematics is the low ability of mathematical communication skills. This causes the students to become not confidence in teaching mathematics-related materials in primary schools, especially in the high class. Based on the observations of researchers, so far, in learning related to the field of mathematics, lecturers explain more and give examples and how to work, then students are asked to work on related problems. This turned out to give a bad impact for students, the impact of students' mathematical communication skills turned out to be less developed. Based on previous research, it is known that one of the efforts to develop students' mathematical communication ability is to apply active learning model. Researchers tried to apply this model of learning in the classroom for 3 meetings, then analyzed matters relating to the applied model. From the results of the study note that the active learning model applied by researchers can run well enough. In the third meeting it was found that 71.4% of the group had been able to represent the answers well and thoroughly. 92,8% or 13 group can hear guidance and direction well, 78,6% group have been able to read problem with good understanding of math, 92,8% group can discuss well, and 71,4% group have been able to express and write the idea into the form of a mathematical symbol.